Effect of a dual compatibilizer on the formation of co-continuous morphology of immiscible po`lymer blends. (5th October 2016) - Yu, Changjiang; Shi, Dean; Wang, Jiang; Shi, Hengchong; Jiang, Tao; Yang, Yingkui; Hu, Guo-Hua; Li, Robert K.Y.
Abstract: This work aims at investigating the effect of a dual compatibilizer on the formation of co-continuous morphology of immiscible polymer blends. More specifically, the blend is composed of polystyrene (PS) and polyamide 6 (PA6), and the dual compatibilizer is composed of a low molecular weight styrene- co -maleic anhydride copolymer (Mw = 11.500 g/mol, maleic anhydride MAH content = 14 wt%) denoted as l SMA and a high molecular weight SMA denoted as h SMA. The latter has a Mw of 250, 000 g/mol and a MAH content of 8 wt% ( h SMA1) or a Mw of 110, 000 g/mol and a MAH content of 23 wt% ( h SMA2). When the PA6 is the minor phase, the morphology of the PS/PA6 blend is co-continuous using the l SMA- h SMA ( h SMA can be h SMA1 or h SMA2) dual compatibilizer. However, when the PA6 is the major phase, its morphology is co-continuous only for the l SMA- h SMA2 dual compatibilizer and not for the l SMA- h SMA1 one. This could be due to fewer PA6 grafts in the in-situ formed h SMA1-g-PA6 graft copolymer and consequently less entanglements of the PA6 grafts with the PA6 major phase compared to the in-situ formed h SMA2-g-PA6 graft copolymer. Graphical abstract: Highlights: A dual compatibilizer composed of a graft copolymer with a short trunk chain and long grafts and another one with a long trunk chain and long grafts favors the formation of co-continuous morphologies of immiscible polymer blends. The graft copolymer with a short trunk chain thermodynamically favors the formation of flat interfaces while the latter mechanically favors the shear stress transfer from matrix to dispersed phase. The former alone is not enough to form co-continuous morphologies because it cannot ensure effective shear stress transfer from matrix to dispersed phase due to weak interfacial entanglements. A certain amount of the graft copolymer with a long trunk chain must be added to ensure effective shear stress transfer from the matrix to dispersed phase.